Uma viagem pelo autoconhecimento: A aventura de um professor estagiário na busca da sua individualidade - João Marcelo Valente Silva (2020)
The Professional Training is an important component of the training of students enrolled in 2nd cycle in Teaching Physical Education in Primary and Secondary School, where the trainee student is inserted in the teaching community and builds his identity as a teacher. This report shares the experiences of a student trainee on his adventure in a school context (Professional Training) with the support of his allies (cooperating teachers and internship nucleus). The report is divided into three major chapters: biographical, institutional and operational framework. The first chapter describes the main character and his expectations, the second chapter portrays the context in which the professional training is inserted and the third chapter addresses the strategies, operationalization and evaluation of teaching, the participation of the trainee student in the school community and his research project. An adventure marked by the personal and professional transformation of the trainee student who started from a point of uncertainty and insecurity, but which grew with overcoming obstacles and learning from his own mistakes. With the help of his allies, the trainee student becomes more confident and gains autonomy to overcome his missions alone. The professional training marks a journey of learning, overcoming and self-discovery that are essential for the construction of the future Physical Education teacher.